In search of lost attachments: Kraemer, S and Roberts, J (eds) (1996) The politics of attachment: Towards a secure society. London: Free Association Books. ISBN 1-85343-344-6 pbk. 254 pages - Tilley, Sue (PINS-Psychology in Society, 2026)
The essential theme of this collection of essays is an exploration of the extent to which the theory of attachment can inform modern political principles and policy The basic claims of the theory - that the quality of early attachment for infants is a key to their developing into integrated people - is transposed to the broader social world. The hypothesis is that for individuals to fully develop in all their capacities, the social context in which they exist must be conducive. The essays are aimed at exploring the implications of this suggestion and range from theoretical considerations of attachment theory itself to the implications for welfare and voluntary activity in civil society, including a number of detailed case studies. In the words of the editors: “The purpose of this book is to add to the prevailing political language an account of what we know about fundamental human needs and so renew our confidence in the possibility of more complex yet more cohesive societies” (p1).